Collaboration with Business Partners and Business Performance: The Role of Relational Competitive Advantage - Sitaniapessy, Rainier Hendrik; Huwae, Victor E (AIBPM Publisher, 2023)
This research stems from the existence of research gaps in collaboration with business partners and business performance. To fill this gap, we developed the concept of Relational Competitive Advantage. This study uses a sample of 120 respondents who are small entrepreneurs, using the purposive sampling technique and AMOS-SEM analysis technique. The results of this study indicate that companies can develop Relational Competitive Advantages that will produce high business performance. The three hypotheses, collaboration with partners and relationship market orientation, positively affect relational Competitive Advantage. Relational Competitive Advantage has a positive effect on Business Performance. All hypotheses have a significant effect, except collaboration with partners. The results of this study also explain the contributions and managerial implications.